2019
DOI: 10.1039/c9sc03781k
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-acidity activated surface charge conversion of two-photon fluorescent nanoprobe for enhanced cellular uptake and targeted imaging of intracellular hydrogen peroxide

Abstract: A smart, two-photon fluorescent GC–NABP nanoprobe with pH-dependent surface charge conversion was developed for tumor-targeted visualization of H2O2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…Among various physicochemical properties of NDDSs, one of dominant factors is the surface charge which control various biological responses to delivery systems. Studies have demonstrated that the electrostatic interactions between the charged nanocarriers with the cytomembrane are of great importance for the cellular uptake, positively charged nanocarriers usually achieved better internalization and higher cellular uptake efficiency than negatively charged ones [ 26 28 ]; however, the positive surface charge did trigger the rapid clearance of NDDSs from blood circulation at the same time. The electrostatic attraction between the negatively charged albumin and those positively charged nanoparticles is the main reason for the clearance of cationic nanocarriers [ 29 , 30 ].…”
Section: Effect Of Surface Charge On the Uptake Of Nanocarriersmentioning
confidence: 99%
“…Among various physicochemical properties of NDDSs, one of dominant factors is the surface charge which control various biological responses to delivery systems. Studies have demonstrated that the electrostatic interactions between the charged nanocarriers with the cytomembrane are of great importance for the cellular uptake, positively charged nanocarriers usually achieved better internalization and higher cellular uptake efficiency than negatively charged ones [ 26 28 ]; however, the positive surface charge did trigger the rapid clearance of NDDSs from blood circulation at the same time. The electrostatic attraction between the negatively charged albumin and those positively charged nanoparticles is the main reason for the clearance of cationic nanocarriers [ 29 , 30 ].…”
Section: Effect Of Surface Charge On the Uptake Of Nanocarriersmentioning
confidence: 99%
“…107 Among the different ROS, hydrogen peroxide (H 2 O 2 ) is a well-known ROS that plays an essential role in physiology, health, and aging in living beings. 108,109 In this view, Kim and co-workers reported a TPA probe, SHP-Mito, for the ratiometric detection of mitochondrial H 2 O 2 . 107 SHP-Mito consisted of a naphthalene derivative as a TP active moiety, boronate-based carbamate as a H 2 O 2 active site, which also acted as a leaving group upon reaction with H 2 O 2 , and triphenylphosphonium as the mitochondrial-targeting site (Fig.…”
Section: Two-photon Probes For Intracellular Sensing and Imaging Of I...mentioning
confidence: 99%
“…In recent years, nanoparticles used to improve the photostability and biocompatibility of small organic molecules have attracted increasing attention in the elds of biosensing, in vivo imaging and drug release. [35][36][37][38] In addition, it has been reported that the selectivity can be improved by encapsulating an organic uorescent probe in a self-assembled supramolecular system of an amphiphilic polymer. 39 In order to achieve the application in a complex living system, we tried to encapsulate the small (DSPE-PEG2000) and poly(ethylene glycol)-block-poly(propylene glycol)-block-poly(ethylene glycol) (mPEG-PPG-PEG) were applied to prepare the nano-probes, respectively (Fig.…”
Section: Construction Of the Ratiometric Uorescent Nano-probementioning
confidence: 99%